PNPT1-mtRNA axis mediates chemotherapy-induced immune signaling and can be targeted to overcome therapeutic resistance - Tian, Mingfu; Liu, Siyu; Li, Xu; Chai, Zelin; Li, Zhiqiang; Fan, Hong; Zhu, Chengliang; Wu, Kailang; Lan, Ke (浪淘沙预印本平台, 2026)
Immunity against malignant cells and the ability of cancer cells to escape anticancer immunity constitute the core process of tumor development, but the underlying mechanism is still largely unknown. Through integrated analyses of clinical samples, cellular assays, and multiple murine tumor models, our study provides compelling evidence that mitochondrial RNA (mtRNA)-derived danger signals potently activate antitumor immunity and uncovers a tumor-specific mechanism for dampening mtRNA-mediated immune responses. Mechanistically, antitumor therapies facilitate the release of immunogenic mitochondrial double-stranded RNA, which potently activates the MAVS signaling cascade and elicits robust antitumor immune responses. Notably, the pan-tumoral expression of MAVS and its upstream receptors enables broad-spectrum mtRNA-driven immune activation across diverse cancer types. In contrast, malignant cells and tumor microenvironments upregulate PNPT1 to degrade immunogenic mitochondrial RNA structures, forming a negative feedback loop that subverts immune surveillance. Importantly, pharmacological inhibition of PNPT1 synergizes with BH3-mimetic drugs to potently amplify mtRNA-mediated antitumor immunity, overcoming therapeutic resistance without apparent systemic toxicity. Our findings suggest that inducing mtRNA-related danger signals in combination with PNPT1 inhibition holds promise as an innovative strategy for anticancer therapy.